(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Although the dissemination of environmental provisions in national constitutions is by now a consolidated phenomenon at a global level, it remains to be seen whether the adoption of these clauses actually increased the weight of environmental reasoning in the balancing process with other constitutional values. In order to assess the effectiveness of these provisions, this paper aims to analyze how constitutional clauses have been used by the parties or by the judges in climate litigations up to now. Some diachronic and synchronic classifications of these cases will then be proposed, according to the type of judgments in which the constitutional norms have been invoked and to the content of the environmental clauses deployed in those litigations.